From Data to Knowledge to Action: A Global Enabler for the 21st Century - Horvitz, Eric; Mitchell, Tom (Computing Community Consortium, 2010)
A confluence of advances in computer science has unleashed unprecedented capabilities for enabling true evidence-based decision making. These capabilities are making possible the large-scale capture of data and the transformation of that data into insights and recommendations in support of decisions about challenging problems in science, society, and government. Key advances include jumps in the availability of rich streams of data, precipitous drops in the cost of storing and retrieving massive amounts of data, exponential increases in computing power and memory, and jumps in the prowess of methods for performing machine learning and reasoning. These advances have come together to create an inflection point in our ability to harness large amounts of data for generating insights and guiding decision making. In this introduction to the Data Analytic Series of whitepapers from the Computing Community Consortium, we discuss the long-term promise of harnessing pipelines of analysis that can provide insights to decision makers and enhance the quality of actions and policies.
Data Analytic Series